2023
DOI: 10.1002/alr.23148
|View full text |Cite
|
Sign up to set email alerts
|

Psychophysical assessment of olfactory and gustatory function in post‐mild COVID‐19 patients: A matched case‐control study with 2‐year follow‐up

Abstract: BackgroundThe aim of this study was to psychophysically evaluate the prevalence of smell and taste dysfunction 2 years after mildly symptomatic severe acute respiratory syndrome–coronavirus‐2 (SARS‐CoV‐2) infection compared to that observed at 1‐year follow‐up and while considering the background of chemosensory dysfunction in the no‐coronavirus disease 2019 (COVID‐19) population.MethodThis is a prospective case‐control study on 93 patients with polymerase chain reaction (PCR)‐positive SARS‐CoV‐2 infection and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
27
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 77 publications
0
27
0
Order By: Relevance
“…Human olfaction has long been considered a neglected sense and the recent COVID-19 pandemic has highlighted the scarce knowledge we have of human olfactory physiology. The sudden and widespread olfactory loss experienced during the pandemic caught us unprepared, with many individuals struggling to recover their sense of smell [1][2][3][4][5][6][7] . Indeed, although the morphology of the human olfactory epithelium was well known, there was limited knowledge about the molecular and functional landscape of different cell types within the human olfactory epithelium.…”
Section: Introductionmentioning
confidence: 99%
“…Human olfaction has long been considered a neglected sense and the recent COVID-19 pandemic has highlighted the scarce knowledge we have of human olfactory physiology. The sudden and widespread olfactory loss experienced during the pandemic caught us unprepared, with many individuals struggling to recover their sense of smell [1][2][3][4][5][6][7] . Indeed, although the morphology of the human olfactory epithelium was well known, there was limited knowledge about the molecular and functional landscape of different cell types within the human olfactory epithelium.…”
Section: Introductionmentioning
confidence: 99%
“…
To the Editor:Boscolo-Rizzo et al 1 concluded that although a proportion of patients recovered from enduring smell/taste dysfunction more than 1 year after coronavirus disease 2019 (COVID-19), some cases still showed a noteworthy remaining olfactory dysfunction 2 years after severe acute respiratory syndrome-coronavirus-2 (SARS-CoV-2) infection compared to matched normal subjects.Initial reports stated that the most frequent symptoms of COVID-19 infection were fever, cough, dyspnea, and myalgia or fatigue. 2,3 Several authors later described an association between COVID-19 and altered olfactory and taste functions.
…”
mentioning
confidence: 99%
“…Boscolo-Rizzo et al 1 concluded that although a proportion of patients recovered from enduring smell/taste dysfunction more than 1 year after coronavirus disease 2019 (COVID-19), some cases still showed a noteworthy remaining olfactory dysfunction 2 years after severe acute respiratory syndrome-coronavirus-2 (SARS-CoV-2) infection compared to matched normal subjects.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This may place subjects at risk of exposure to environmental hazards. 4 Thus, a complete orthonasal evaluation of the olfactory function, including identification, discrimination, and threshold subtests, is crucial.…”
mentioning
confidence: 99%